El Inti Raymi, Kulla Raymi, Pawkar Raymi y su influencia en la cotidianidad de los habitantes de la parroquia Punin, cantón Riobamba, provincia de Chimborazo en el 2014. - Abarca Tenelanda, Washington Jesús (2016)
The socio-cultural development of mankind demands the involvement into investigative studies to determine the achievements and limitations of evolutionary processes in societies in order to rescue, assess and develop socio-cultural activities like the “Inti Raymi”, “Kulla Raymi” and “Pawkar Raymi” to entrench the customs and traditions in the residents of Punín in a community called “San José de Chalan” which is located in Riobamba, province of Chimborazo; at the end of this study, it has been identified that sociocultural and ancestral festivities in Ecuador contribute in the development and conservation of traditions, as these strengthen the cultural identity of various ethnic groups around the country as each of them are identified as the oldest renowned throughout the Inca community in Ecuador, Peru and Bolivia. By applying research methods, the direct participation of residents in Punín in a community called “San José de Chalan” could be demonstrated as these cultural events pretend to protect the cultural heritage of its residents raising the people self-esteem, valuing their traditions and recommendations are presented where the inhabitants of Punín represent the ancestral ethnic identity, with the preactice of “Inti Rymi”, “Kulla Raymi” and “Pawkar Raymi”.